2008
DOI: 10.1016/j.heares.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mitochondrial energetic dysfunction on apoptosis in outer hair cells of the cochlea following exposure to intense noise

Abstract: Previous studies have shown that exposure to intense noise causes outer hair cells (OHCs) to die, primarily through the process of apoptotic degeneration. The current study was designed to examine the regulatory role of mitochondrial bioenergetic function in controlling the initiation and execution of the apoptotic process of OHCs. Chinchilla cochleae were treated with 3-nitropropionic acid (3-NP, 20 mM, or 50 mM), an irreversible inhibitor of succinate dehydrogenase (SDH), to inhibit the mitochondrial energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Cisplatin significantly increased the active caspase-3 and Bax protein expression, but decreased Bcl-2 protein expression in the rat cochleae [32], which was in line with our study. Noise exposure results in hair cell death primarily through apoptosis [33]. Several noise-induced events, including calcium influx, ATP depletion, and oxidative stress, play a role in exacerbating the pathological responses of sensory cells [34].…”
Section: Control Cisplatin Model Relative Protein Expressionmentioning
confidence: 99%
“…Cisplatin significantly increased the active caspase-3 and Bax protein expression, but decreased Bcl-2 protein expression in the rat cochleae [32], which was in line with our study. Noise exposure results in hair cell death primarily through apoptosis [33]. Several noise-induced events, including calcium influx, ATP depletion, and oxidative stress, play a role in exacerbating the pathological responses of sensory cells [34].…”
Section: Control Cisplatin Model Relative Protein Expressionmentioning
confidence: 99%
“…ROS accumulation and mitochondrial dysfunction have been reported to be involved in HC apoptosis (Hu et al, 2008;He et al, 2016). ROS accumulation leads to mitochondrial depolarization, which results in a decrease in the MMP and the subsequent release of apoptotic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are specialized organelles that produce most of the cell's energy (Alberts et al , ). Changes in mitochondrial respiration (Hu et al , ; Crawley & Keithley, ; Park et al , ) and activation of a mitochondrial cell death pathway (Wang et al , ) have been reported in mammalian hair cells following sound trauma. Additionally, the transcript encoding C14orf159 is up‐regulated in S .…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are specialized organelles that produce most of the cell's energy (Alberts et al, 2008). Changes in mitochondrial respiration (Hu et al, 2008;Crawley & Keithley, 2011;Park et al, 2012) and activation of a mitochondrial cell death pathway (Wang et al, 2007) have been reported in mammalian hair cells following sound trauma. Additionally, the transcript encoding C14orf159 is up-regulated in S. salar gill affected by amoebic gill disease immediately following exposure to virulent amoebae (Morrison et al, 2006), and the human c14orf159 gene is known to bind ER in 17 -oestradiol-treated human breast cancer cells (Creekmore et al, 2007).…”
Section: S T Ru C T U R a L G E N E Smentioning
confidence: 99%